2016
DOI: 10.7314/apjcp.2016.17.2.667
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Suppresses Proliferation of Human Ovarian Cancer Cells via Blockage of mTOR Signaling

Abstract: Oridonin, an ent-kaurane diterpenoid compound isolated from the traditional Chinese herb Rabdosia rubescens, has shown various pharmacological and physiological effects such as anti-tumor, anti-bacterial, and anti-inflammatory properties. However, the effect of oridonin on human ovarian cancer cell lines has not been determined. In this study, we demonstrated that oridonin inhibited ovarian cancer cell proliferation, migration and invasion in a dose-dependent manner. Furthermore, we showed oridonin inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Numerous studies show that oridonin can suppress cell growth and induce cell-cycle arrest in a variety of cancer cell lines (2,5,6). Oridonin also causes a reduction in cell proliferation through induction of death receptor 5 and suppression of mammalian target of rapamycin (mTOR) phosphorylation in breast and ovarian cancer cells (13,14). In the present study, we investigated whether oridonin has growth inhibitory activity in human oral cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies show that oridonin can suppress cell growth and induce cell-cycle arrest in a variety of cancer cell lines (2,5,6). Oridonin also causes a reduction in cell proliferation through induction of death receptor 5 and suppression of mammalian target of rapamycin (mTOR) phosphorylation in breast and ovarian cancer cells (13,14). In the present study, we investigated whether oridonin has growth inhibitory activity in human oral cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that Oridonin can specifically inhibit NLRP3 inflammasome activation, where NACHT domain and Oridonin share cysteine 279 binding site ( 114 ). The ability of Oridonin to suppress cell proliferation was previously demonstrated in breast ( 133 ) ovarian ( 115 ) and esophageal ( 116 ) cancers. On the other hand, CY-09 ( 117 ), OLT1177( 118 , 119 ), Tranilast ( 120 , 121 ) present as promising specific NLRP3 inhibitors.…”
Section: Therapeutic Potential Of Targeting Nlrp3 Inflammasome In Canmentioning
confidence: 88%
“…CCL18 induced OC invasiveness is strongly connected with mTORC2 [ 69 ]. Blockage of mTOR signaling results in suppression of proliferation of OC [ 70 ]. mTOR increases OC cells viability and decreases their apoptosis and autophagy [ 71 ].…”
Section: Interrelation Of Pi3k/akt/mtor and Pim Pathways In Ovariamentioning
confidence: 99%